Analisis Sosiologis Reintegrasi Sosial Klien Pemasyarakatan - Lovita Nurindah Sari (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2021)
The Social Reintegration Program in Correctional facilities is not only aimed to reduce number of prisoners. But so far social reintegration aims at recovering the relationship, livelihood and life of WBP. WBP who get social reintegration programs such as Asimilasi Rumah, Cuti Bersyarat, Pembebasan Bersyarat, and Cuti Menjelang Bebas get guidance and supervision from the Correctional Center which is the responsibility of the social Advisers in the institution. This study based on qualitative descriptive method with the subject of Bapas Pamekasan clients who were selected by purposive sampling(adjusted to the research problem).The theory in this study is 4 dimensional elements in social research consisting of individual characteristics, (b) family relationships, (c) community context, and (d) state policy. Based on The results of the research, the Social Reintegration of Correctional Clients is a process of guidance and supervision carried out by the Social Adviser which has not been optimally implemented in accordance with the goal of life recovering, livelihood and life of the WBP. Social reintegration should be seen as a process of adjustment to the Correctional Client so that his relationship can be recovered socially and economically. The 4 Dimensions in social Research Balai Pemasyarakatan carried out by PK Bapas must be recreated after he gets Social Reintegration because the 4 dimensions are dynamic. This 4-dimensional approach in society research is the initial base for PKs to carry out guidance and supervision for those built by Social Reintegration. Keywords: Social Reintegration, 4 dimensions of Litmas (Society Research), Client Guidance